THE INFLUENCE OF PRICES AND PRODUCTS ON PURCHASE DECISIONS AT PAKDE SURIPAN MEATBALL STALLS - Muhammad Bayu; Sukardi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the influence of prices and products on consumer purchase decisions at Warung Bakso Pakde Suripan, Mukok District, Sanggau Regency. The background of this study is based on the increasing competition in the meatball culinary business in the region, which encourages business actors to optimize their price and product quality strategies. The research method used was an associative quantitative approach with purposive sampling techniques on 100 respondents who had made purchases. Data were collected through a Likert scale questionnaire and analyzed using validity, reliability, multiple linear regression tests, as well as F tests and t tests. The results showed that both price and product had a significant effect simultaneously and partially on purchase decisions, with the product having a dominant influence (β = 0.731; Sig. = 0.000) over price (β = 0.187; Sig. = 0.005). The coefficient of determination (R² = 0.728) indicates that 72.8% of the variation in purchasing decisions can be explained by both independent variables. These findings provide strategic implications for the management of local culinary businesses in increasing competitiveness and consumer satisfaction.